Modulating effects of RAMPs on signaling profiles of the glucagon receptor family - Lijun Shao; Yan Chen; Shikai Zhang; Zhihui Zhang; Yongbing Cao; Dehua Yang; Ming-Wei Wang (Elsevier, 2022)
Receptor activity-modulating proteins (RAMPs) are accessory molecules that form complexes with specific G protein-coupled receptors (GPCRs) and modulate their functions. It is established that RAMP interacts with the glucagon receptor family of GPCRs but the underlying mechanism is poorly understood. In this study, we used a bioluminescence resonance energy transfer (BRET) approach to comprehensively investigate such interactions. In conjunction with cAMP accumulation, Gαq activation and β-arrestin1/2 recruitment assays, we not only verified the GPCR-RAMP pairs previously reported, but also identified new patterns of GPCR-RAMP interaction. While RAMP1 was able to modify the three signaling events elicited by both glucagon receptor (GCGR) and glucagon-like peptide-1 receptor (GLP-1R), and RAMP2 mainly affected β-arrestin1/2 recruitment by GCGR, GLP-1R and glucagon-like peptide-2 receptor, RAMP3 showed a widespread negative impact on all the family members except for growth hormone-releasing hormone receptor covering the three pathways. Our results suggest that RAMP modulates both G protein dependent and independent signal transduction among the glucagon receptor family members in a receptor-specific manner. Mapping such interactions provides new insights into the role of RAMP in ligand recognition and receptor activation.